Intravenous immunoglobulin treatment for patients with severe COVID-19: a retrospective multicentre study. (October 2021) - Liu, Jiao; Chen, Yizhu; Li, Ranran; Wu, Zhixiong; Xu, Qianghong; Li, Zhongyi; Annane, Djillali; Feng, Huibin; Huang, Sisi; Guo, Jun; Zhang, Lidi; Ye, Xiaofei; et al.
Abstract: Objectives: Intravenous immunoglobulin (IVIG) is commonly used to treat severe COVID-19, although the clinical outcome of such treatment remains unclear. This study evaluated the effectiveness of IVIG treatment in severe COVID-19 patients. Methods: This retrospective multicentre study evaluated 28-day mortality in severe COVID-19 patients with or without IVIG treatment. Each patient treated with IVIG was matched with one untreated patient. Logistic regression and inverse probability weighting (IPW) were used to control confounding factors. Results: The study included 850 patients (421 IVIG-treated patients and 429 non-IVIG-treated patients). After matching, 406 patients per group remained. No significant difference in 28-day mortality was observed after IPW analysis (average treatment effect (ATE) = 0.008, 95% CI –0.081 to 0.097, p 0.863). There were no significant differences between the IVIG group and non-IVIG group for acute respiratory distress syndrome, diffuse intravascular coagulation, myocardial injury, acute hepatic injury, shock, acute kidney injury, non-invasive mechanical ventilation, invasive mechanical ventilation, continuous renal replacement therapy and extracorporeal membrane oxygenation except for prone position ventilation (ATE = –0.022, 95% CI –0.041 to –0.002, p 0.028). Discussion: IVIG treatment was not associated with significant changes in 28-day mortality in severe COVID-19 patients. The effectiveness of IVIG in treating patients with severe COVID-19 needs to be further investigated through future studies.